Evaluating parliamentary advocacy for nutrition in Tanzania - te Lintelo, D. J. H.; Pittore, K. (Springer, 2021)
The global nutrition community is currently putting significant efforts into supporting parliamentary advocacy, aiming to bring nutrition higher up on political agendas in low-income countries with high burdens of malnutrition. Evaluating the effects of parliamentary advocacy is fraught with methodological challenges and case studies are scarce. This article adopts a contribution analysis and process tracing procedure to evaluate whether parliamentary advocacy influenced political party manifestos in Tanzania in the run up to the 2015 general election. We present a rare and empirically rich application of this systematic qualitative evaluative method. We find that configurations of activities, actors and outputs can be plausibly understood to have had a contributory role in achieving increased attention to nutrition in the party manifesto of the election winner. We further identify key risks and assumptions that mediated parliamentary advocacy and development evaluators’ ability to evaluate its outcomes, including: targeting; timing; circulation; intelligibility; power; elites; resources; and political space.